Orientasi Manajemen Sumberdaya Arkeologi di Indonesia - M. Nur (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
The archaeological resources distribute almost in the whole area of Indonesia. The condition of archaeological resources management in our country still under standard. Good concept, theory and the operational at archaeological resources management in a country must have a good relation with the progress at conflict management and its partipatoris approach. Basicly, the state determination to archaeological resources management could be done right as long as all the public interest can be accommodate. The effective way to make it is how to involve the public into the activities.